2016
DOI: 10.1080/15622975.2016.1265147
|View full text |Cite
|
Sign up to set email alerts
|

Increased deficits in emotion recognition and regulation in children and adolescents with exogenous obesity

Abstract: Improved understanding of emotional recognition and emotion regulation in young people with obesity may improve their social adaptation and help in the treatment of their disorder. To the best of our knowledge, this is the first study to evaluate both emotional recognition and emotion regulation functions in obese children and obese adolescents between 11 and 18 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Our results extend those reported in a recent study (Percinel et al, ) showing lower performance in the RME related to obesity in a sample of children and adolescents. Our results partially agree with those described by Percinel et al (), because our subjects with obesity also showed a lower performance in the test. However, in our study, patients with obesity showed reduced performance only in the identification of negative stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results extend those reported in a recent study (Percinel et al, ) showing lower performance in the RME related to obesity in a sample of children and adolescents. Our results partially agree with those described by Percinel et al (), because our subjects with obesity also showed a lower performance in the test. However, in our study, patients with obesity showed reduced performance only in the identification of negative stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported impaired theory of mind in anorexic patients (Russell, Schmidt, Doherty, Young, & Tchanturia, ; Tapajóz Pereira de Sampaio, Soneira, Aulicino, & Allegri, ), whereas it seems to be preserved in patients with bulimia (DeJong et al, ; Tapajóz Pereira de Sampaio et al, ). Following a procedure similar to ours, a recent study has reported difficulties in children and adolescents with obesity in understanding others' mental states from eye gaze (Percinel, Ozbaran, Kose, Simsek, & Darcan, ), but data from adult population with obesity are lacking.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Aloi et al [6] observed a comparable capability to recognize others' emotions but impaired ability in defining and analyzing their self emotions when compared with non-BED patients with obesity. Percinel et al [25] found that children with obesity had lower scores for all kinds of social cognition task compared with healthy controls. Our findings are partly consistent with the outcomes of other study results.…”
Section: Discussionmentioning
confidence: 99%
“…FPT tasks are considered as a good measurement tool of second-stage ToM impairments; in these tests it is stated that the skill of the person indicates the severity of the mental disorder. Good interrater reliability was demonstrated in a thesis study conducted in Turkey [25].…”
Section: Emotional and Social Cognition Assessmentmentioning
confidence: 95%
See 1 more Smart Citation